Isolation of endophytic fungi from agarwood - Lai, Kim Kee. (Universiti Malaysia Sarawak (UNIMAS), 2015)
Agarwood, or gaharu in Malaysia, is one of the traditional woods that is highly demanded by the world market population. It is widely used in the production of medicine, perfume, and incense. The production of agarwood is occurred due to fungal infection on agarwood tree. Over the years, scientists found out that this agarwood has antimicrobial compounds which believe to give an immune response towards the infection. Therefore, the purpose of this project is to isolate the endophytic fungi that can produce secondary metabolites for antimicrobial activity from agarwood. Samples were surface sterilized in order to isolate the endophytic fungi. The samples were grown on potato-dextrose agar (PDA) to get the pure isolate. Eleven pure isolates obtained were expected to belong to five species, namely Trichoderma harzanium, Trichoderma reesei, Trichoderma spp., Beauveria bassiana, Botryodiplodia theobromae, and one unknown species. The confirmed endophytes were analysed by polymerase chain reaction (peR) amplification targeting on the ITSrRNA region and sequencing to establish their identity. A further study on the screening of endophytic fungi should be carried out in order to find out the-potential metabolites produced for novel antimicrobial drug manufacture